A comparative analysis of state adoption of the Community First Choice program. Issue 3 (3rd July 2021) - Beauregard, Lisa Kalimon; Miller, Edward Alan
ABSTRACT: Over the last several decades, policymakers have focused on rebalancing Medicaid-funded long-term services and supports toward home and community-based services (HCBS). The Patient Protection and Affordable Care Act (ACA) included several opportunities for states to further promote HCBS options. One optional opportunity for states to expand Medicaid HCBS was the 1915(k) Community First Choice (CFC) program. To date, eight states have elected to add CFC as a Medicaid benefit. This study utilized comparative case studies to identify the factors that influenced states' adoption of CFC. Results highlight the important role that state bureaucrats, economic concerns, and existing HCBS programs had on states' decisions to adopt CFC.